ESTUDO DAS REAÇÕES DE OXIDAÇÃO DE METANOL E ETANOL SOBRE CATALISADORES BI E TRIMETÁLICOS ATRAVÉS DE TÉCNICAS DE VOLTAMETRIA CÍCLICA E DEMS - Silva, Quésia Guedes da (2006)
The interest in the use of methanol and ethanol as fuels in a fuel cell is justified by the search for new energy conversers, more efficient and less polluters. This work presents the study of the oxidation reaction these alcohols on catalysts obtained by potentiostatic deposition of Pt or codeposition of PtRu, PtRuSn e PtSn using as subtract a Teflon membrane GORE-TEK with sputtering of 600nm of gold and a geometric area of 1,11cm2. The reference electrode used was the reversible of hydrogen, as an opposite electrode there was a platinum sheet. The experiments were made using the combination of cyclic voltammetry and on line mass spectrometry, called differential electrochemical mass spectrometry (DEMS) The electroposits were examined using X-ray energy dispersive analysis (EDAX) and scanning electron microscopy (SEM) The electrochemistry results have shown that Pt-Ru catalyst presented better catalitic activity to methanol oxidation in lower potentials, showing the following sequence to catalitic activity: PtRu > PtRuSn @ PtSn > Pt. The mass spectrometry data have shown similar results with better performance to PtRu electrode in the CO2 (m/z = 44) production. In the case of the ethanol oxidation the electrochemistry data show that the catalyst Pt-Sn and Pt-Ru- Sn were the most active in lower potentials. The mass spectrometry results have shown that, when compared with others, the PtSn electrode presents greater activity both in the CO2 production as well as in the acetaldehyde s.